TRANSFORMATION OF VISUAL STEREOTYPES ON TV: NONFICTIONAL TV-FORMATS OF THE USA AND CANADA OF THE 1960th / Трансформация зрелищных стереотипов на малом экране: неигровые телеформаты США и Канады 1960-х годов - KAZYUCHITS M.F. / КАЗЮЧИЦ М.Ф. (Наука телевидения)
The experiments of documentary film makers of the USA, Canada and European countries made in 1950–1960 on the basis of new technologies and in the conditions of competitive fight of cinema and TV are analyzed in the article. At that time the image of an anthropomorphous camera, the camera-eye often appeared in the names of documentaries and TV programs, as if it was living its own life, sometimes different from the human one (“Candid eye”, “Candid camera”, “Living camera” etc.). “Cinéma vérité”—the term for the first time used by the French sociologist, the theorist of cinema E. Moren represents, as we know, the translation of the name of the well-known newsreel “Film truth” which was issued in the 1920th under the supervision of Vertov. In 1950– 1960th the term found its own cultural specifications: for example, “direct cinema”. Traditionally connected with cinéma vérité, the screen documentary of the USA significally depended on ideology—tactical require-ments, “policy” of a TV-broadcaster and market condi-tions of creation and distribution of TV production. Documentary film makers of the USA (Drew Associates group—R. Drew, R. Leacock, D. Pennebaker, etc.) and Canada (R. Kroitor, W. Koenig, C. Low) became pioneers in the field of a new “non-European” television wave who founded the base of application of a method of the extended (participant) observation, thereby having opened a way to a wide range of formats from author’s documentary to reality-TV. Soon both directions, direct cinema and cinéma vérité with all their originality were widely spread in their own style (cinema or TV feature), as well as a shooting style in general. Thus theoretical and practical researches of docu-mentary film makers of the USA, Canada and European countries on the basis of new technologies, competitive struggle of cinema and TV allowed to introduce new methods. The last ones gave the chance to create new experience of esthetic perception of screen material at target audiences that in turn caused considerable complication of the discourse side of screen work; these very methods gave it almost equal importance with a narrative. This difficult connection of a discourse and a narration considerably complicating broadcasting and interpretation of the author’s concept, in many ways is an essential feature of modern screen culture, fictional and nonfictional formats of television and cinema.